Respuesta :
Answer:
2
Step-by-step explanation:
using the rules of logarithms
logx + logy = log(xy)
logx - logy = log ([tex]\frac{x}{y}[/tex] )
log[tex]x^{n}[/tex] ⇔ nlogx
[tex]log_{b}[/tex] x = n ⇒ x = [tex]b^{n}[/tex]
given
3log2 + log200 - log16
= log 2³ + log200 - log16
= log8 + log200 - log16
= log(8 × 200) - log16
= log1600 - log16
= log ([tex]\frac{1600}{16}[/tex] )
= log100
let [tex]log_{10}[/tex] 100 = n , then
100 = [tex]10^{n}[/tex] = 10²
thus value of expression is n = 2 , that is 2
[tex]2 \cdot 1[/tex]Answer:
Equal to 2
Step-by-step explanation:
1. Apply log rule: [tex]alog_c(b) = log_{c}(b^a)[/tex]
[tex]3log_{10}(2) = log_{10}(2^3)[/tex]
[tex]= log_{10}(2^3) + log_{10}(200) - log_{10}(16)[/tex]
2. Apply log rule: [tex]log_c(a) + log_c(b) = log_c(ab)[/tex]
[tex]log_{10}(2^3) + log_{10}(200) = log_{10}(2^3 \cdot 200)[/tex]
[tex]= log_{10}(2^3 \cdot 200) - log_{10}(16)[/tex]
[tex]2^3 \cdot 200 = 1600[/tex]
[tex]= log_{10}(1600) - log_{10}(16)[/tex]
3. Apply log rule: [tex]log_c(a) - log_c(b) = log_c(\frac{a}{b})[/tex]
[tex]log_{10}(1600) - log_{10}(16) = log_{10}(\frac{1600}{16})[/tex]
Divide the numbers: [tex]\frac{1600}{16} = 100[/tex]
[tex]= log_{10}(100)[/tex]
Rewrite 100 in power - base form: [tex]100 = 10^2[/tex]
[tex]= log_{10}(10^2)[/tex]
4. Apply log rule: [tex]log_a(x^b) = b \cdot log_a(x)[/tex]
[tex]log_{10}(10^2) = 2log_{10}(10)[/tex]
[tex]2log_{10}(10)[/tex]
5. Apply log rule: [tex]log_a(a) = 1[/tex]
[tex]log_{10}(10) = 1[/tex]
[tex]= 2 \cdot 1 = 2[/tex]